Comparative study of AlGaN/GaN heterostructures grown on different sapphire substrates. (October 2019) - Li, Wen; Xu, Shengrui; Zhang, Yachao; Peng, Ruoshi; Zhao, Ying; Du, Jinjuan; Fan, Xiaomeng; Zhang, Jincheng; Tao, Hongchang; Wang, Xuewei; Hao, Yue
Abstract: AlGaN/GaN heterostructures were grown on the conventional planar sapphire substrate (CSS), nano-scale patterned sapphire substrate (NPSS) and micro-scale patterned sapphire substrates (MPSS) by metal organic chemical vapor deposition respectively. The heterostructure grown on the MPSS has significantly lower threading dislocation density (TDD) than those grown on the NPSS and CSS. The bending and quenching of threading dislocations induced by lateral growth are the main factors for the reduction of TDD. Correspondingly, the carrier mobility of heterostructure grown on the MPSS is also the highest. Highlights: The AlGaN/GaN heterostructures grown on different sapphire substrates were achieved. The bending and quenching of threading dislocation induced by lateral growth are the main factors for the reduction of threading dislocation density. The effect of different substrates on surface morphology, crystalline quality, and carrier mobility of AlGaN/GaN heterostructures were investigated in detail.